UMP and CIDB established Building Information Model (BIM) ecosystem - UMP, PNC (2019)
The collaboration between Universiti Malaysia Pahang (UMP) and Malaysia Construction Industry Development Board (CIDB) in creating a Building Industry Model (BIM) ecosystem for national transformation is seen as successful amidst the high impact projects to transform the country’s construction industry worth RM1.4billion that brings about various benefits and changes.